THE DEVELOPMENT OF ELECTRONIC-WORKSHEETS (E-WORKSHEETS) WITH SUB-MATERIALS OF WASTE RECYCLING BASED ON ECOPRENEURSHIP TO TRAIN ENTREPRENEURSHIP INTEREST OF STUDENTS - Saifuddin, Mochammad Yuda; Kuntjoro, Sunu (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2021)
Abstract The 2013 curriculum requires students with productive, innovative, and creative traits that have a positive contribution to social life, for instance by creating graduates who have an entrepreneurial interest to be an ecopreneur. To be able to fulfill these demands, school life-learning is needed, which is supported by decent and appropriate teaching materials in order to increase the entrepreneurial interest of students. The research aims to produce teaching materials in the form of Electronic-Worksheets (E-Worksheets) waste recycling ecopreneurship to instruct students' entrepreneurial interest which is theoretically and empirically feasible in accordance with the requirements of the 2013 curriculum and 21st century learning using the 4D method. (define, design, develop, disseminate) without doing the disseminate stage. Theoretical feasibility is obtained from the validation results, while empirical feasibility is obtained from the results of the teacher response questionnaire. E-worksheets ecopreneurship waste recycling is declared very feasible theoretically with an average value of 3.66 and empirical with an average value of 98%. Keywords: E-worksheets, Entepreneurship, Ecopreneurship, Entrepreneurial Interests, Waste recycling